Dual Business Relationships, Opportunity Knowledge, and New Product Development: A Study on Returnee Young Ventures. Issue 3 (September 2019) - Bai, Wensong; Johanson, Martin; Martín Martín, Oscar
The effects on innovation of the dual embeddedness of returnee young ventures (RYVs) in both domestic and international networks of relationships and knowledge contexts are important for value creation, growth, and success of these firms and embody a unique research opportunity. Drawing on a framework combining a business relationship perspective and the knowledge-based view, the authors propose that RYVs take advantage of business relationships and opportunity knowledge from both international and domestic markets to nurture their innovation. They test their model on a sample of 200 RYVs in China. The findings reveal that business relationships are essential for acquiring knowledge about technological and business opportunities, though only international opportunity knowledge and domestic business relationships positively influence new product development. In addition, the interaction between international and domestic business relationships constrains firms' capacity for obtaining international opportunity knowledge. This study offers insights into how the trade-offs between dual relationships and subsequently sourced knowledge contribute to new product development in emerging markets, and it extends the discussion on the paradox view of business relationships with geographically dispersed actors.